Epidemiology of the classical myeloproliferative neoplasms: The four corners of an expansive and complex map. (July 2020) - Shallis, Rory M.; Wang, Rong; Davidoff, Amy; Ma, Xiaomei; Podoltsev, Nikolai A.; Zeidan, Amer M.
Abstract: The classical myeloproliferative neoplasms (MPNs), specifically chronic myeloid leukemia (CML), polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF), represent clonal myeloid disorders whose pathogenesis is driven by well-defined molecular abnormalities. In this comprehensive review, we summarize the epidemiological literature and present our own analysis of the most recent the Surveillance, Epidemiology, and End Results (SEER) program data through 2016. Older age and male gender are known risk factors for MPNs, but the potential etiological role of other variables is less established. The incidences of CML, PV, and ET are relatively similar at 1.0–2.0 per 100, 000 person-years in the United States, while PMF is rarer with an incidence of 0.3 per 100, 000 person-years. The availability of tyrosine kinase inhibitor therapy has dramatically improved CML patient outcomes and yield a life expectancy similar to the general population. Patients with PV or ET have better survival than PMF patients.